Posterior reversible encephalopathy syndrome - Anjan Trikha; Ankur Sharma; Rakesh Kumar (Wolters Kluwer Medknow Publications, 2014)
Posterior reversible encephalopathy syndrome is a clinicoradiological entity characterized clinically by headache, hypertension, altered sensorium and visual disturbances. It is usually seen in the setting of toxemia of pregnancy, hypertension, severe infection or in patients receiving immunosuppressant's. The magnetic resonance imaging of the brain in such patients reveals bilateral symmetrical subcortical edema in the occipitoparietal region. The treatment is primarily supportive and involves removing the underlying cause. The condition if not identified in time may lead to irreversible damage to the brain such as hemorrhage or infarction.